Golf Tournament strengthens family ties between UA - Mimi Rabita, Abdul Wahit (UMPSA, 2022)
KUANTAN, 29 May 2022 - A total of 300 golfers from public universities (UA) competed in the 49th Public University Golf Tournament held for two days on 28 and 29 May 2022.